2011
DOI: 10.1270/jsbbs.61.86
|View full text |Cite
|
Sign up to set email alerts
|

'Tachisuzuka', a new rice cultivar with high straw yield and high sugar content for whole-crop silage use

Abstract: 'Tachisuzuka' is a new rice (Oryza sativa L.) cultivar for whole-crop silage (WCS) use. Agronomic characters were recorded from 2007 to 2009. The culm length of Tachisuzuka was 11 cm longer than that of Kusanohoshi. The short panicle of Tachisuzuka was morphologically similar to that of the short panicle 1 (sp1) mutant. Tachisuzuka exhibited high lodging resistance in the yellow ripening stage, the optimal period for harvesting, and a month after yellow ripening. The straw yield of Tachisuzuka was remarkably h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 9 publications
1
22
0
Order By: Relevance
“…G6P, F6P, UDPG, ADPG, should be compared between TS and KH. Also the other parental line of TS, Gokutansui (a mutant line with extrashort panicles; Matsushita et al, 2011), would be worth for comparison. To clarify the key factor underlying sugar accumulation in rice stems, further studies such as functional analyses of candidate genes, and analyses using backcross-derived populations of TS, are required.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…G6P, F6P, UDPG, ADPG, should be compared between TS and KH. Also the other parental line of TS, Gokutansui (a mutant line with extrashort panicles; Matsushita et al, 2011), would be worth for comparison. To clarify the key factor underlying sugar accumulation in rice stems, further studies such as functional analyses of candidate genes, and analyses using backcross-derived populations of TS, are required.…”
Section: Resultsmentioning
confidence: 99%
“…Tachisuzuka (TS), a rice cultivar used for whole-crop silage, has a small panicle and high sugar content in the stem (Matsushita et al, 2011). We previously showed that its small panicle is due to the mutation of the SP1 gene (Hirose et al, 2017), which belongs to the NRT1/PTR family (Léran et al, 2014;Li et al, 2009).…”
Section: Plant Materials Growth Conditions and Samplingmentioning
confidence: 99%
“…Biotechnology, andBiochemistry, 75, 1104-1112. rice straw after dilute acid pretreatment using these cultivars were also very high (Goda et al, 2016;Teramura et al, 2013). However, as observed in CRCT overexpression lines, the grain yield of these rice cultivars was significantly low because of their small panicles (Matsushita et al, 2011). Thus, it is considered that there should be trade-off relationship between the glucose content of rice straw and the grain yield.…”
Section: Disclosure Statementmentioning
confidence: 86%
“…These observations probably led to the reduction of grain yield in CRCT overexpression lines. Previous studies demonstrated that 'Tachisuzuka' and 'Leafstar' could accumulate high levels of carbohydrates in stems (Matsushita et al, 2011;Ookawa et al, 2010). The glucose contents in liquid hydrolyzate of hydrolyzate.…”
Section: Effects Of Crct Expression Levels On the Biomass Productionmentioning
confidence: 99%
“…However, there is loss of the nutrients because some of the grain eaten by cattle is excreted in feces without being digested (Yamamoto et al, 2005;Fang et al, 2011). As a solution to this problem, a new rice cultivar with short panicles, 'Tachisuzuka', was developed and released (Matsushita et al, 2011). The short panicles resulted in a markedly low grain/straw ratio, and the milk yield in lactating cattle fed 'Tachisuzuka' silage increased (Kouno, 2011).…”
mentioning
confidence: 99%